2016
DOI: 10.1097/md.0000000000004450
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of FDG-PET/CT for evaluating early response to induction chemotherapy in head and neck squamous cell carcinoma

Abstract: Background: 18F-Fluoro-Deoxy-Glucose Positron Emission Tomography with Computed Tomography (18F-FDG PET/CT) may be a powerful tool to predict treatment outcome. We aimed to review the effectiveness of 18F-FDG PET/CT in the assessment of early response to induction chemotherapy (IC) in patients with advanced Head and Neck Squamous Cell Cancer (HNSCC) without previous treatment.Methods:PubMed, Cochrane Library, Science Direct and Web of Science were searched to May 2016. Reference lists of the included articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In an exploratory study, fifteen patients underwent PET imaging with 18 FDG before and 12 days after starting treatment to determine if FGFR inhibition alters tumor glucose metabolism and if metabolic tumor response correlates with subsequent clinical outcome (27–29). Three patients (20%) had metabolic responses with no discernable changes in tumor size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an exploratory study, fifteen patients underwent PET imaging with 18 FDG before and 12 days after starting treatment to determine if FGFR inhibition alters tumor glucose metabolism and if metabolic tumor response correlates with subsequent clinical outcome (27–29). Three patients (20%) had metabolic responses with no discernable changes in tumor size.…”
Section: Resultsmentioning
confidence: 99%
“…Exploratory analyses included evaluation of early metabolic tumor response rate (day 12), changes in quality of life (QOL), and biomarker studies. Early metabolic responses were defined as 25% reduction in the maximal standard uptake (SUV) of 18F-fluorodeoxyglucose ( 18 FDG) on PET scans done on day 12 as compared to pre-treatment values (27). QOL outcomes were monitored by the FACT-G questionnaires at each clinic visit.…”
Section: Methodsmentioning
confidence: 99%
“…At that time, the role of FDG in the early response assessment was questionable in head and neck cancer. However, recently, in a systematic review, the potential value of F-FDG PET/CT as a diagnostic tool for early response assessment in head and neck cancer patients has been confirmed [32]. …”
Section: Early Response Assessments and Imaging Biomarkersmentioning
confidence: 99%
“…However, 6 of 7 studies concluded that FDG-PET allowed early evaluation response to induction chemotherapy and predicted survival outcomes. 60 The studies cited above demonstrate the potential of FDG-PET to assess response to induction chemotherapy in order to select patients for treatment adaptation (ie, concomitant chemoradiation or surgery). Unfortunately, different parameters have been used for response assessment.…”
Section: De Bree Et Almentioning
confidence: 99%
“…The authors concluded that a meta‐analysis was not possible because the selected studies were heterogeneous concerning response criteria, reference standards, chemotherapy strategy, and endpoints. However, 6 of 7 studies concluded that FDG‐PET allowed early evaluation response to induction chemotherapy and predicted survival outcomes …”
Section: Introductionmentioning
confidence: 99%